Evaluasi Dampak Kegiatan Sekolah Terhadap Pola Lalu Lintas Dan Mobilitas Kota - Prasetyo , Yohanes Pracoyo Widi (CV. Information Technology Training Center - Indonesia (ITTC), 2024)
This research aims to evaluate the impact of school activities on traffic patterns and city mobility by conducting a case study on a secondary school in an urban area. As a case study, the Jalan Tempeh section of Lumajang Regency, which contains SMA Negeri 1 Tempeh Lumajang. Research was conducted to understand how daily school activities, including start and leave times, school events, and extracurricular activities, influence traffic patterns and mobility around the school area. Research methods include field surveys to observe traffic patterns, calculating traffic volume during rush hours, interviews with school officials, and analysis of traffic accident data around the school location. The use of this combination of methods allows us to gain a comprehensive understanding of the impact of school activities on urban traffic and mobility. The research results show that school activities have a significant impact on traffic patterns around the school area, especially during rush hours. Traffic density increases significantly during school entry and exit hours, which has the potential to cause congestion and increase the risk of traffic accidents.